Peroxisome proliferator-activated receptor ligands regulate lipid content, metabolism, and composition in fetal lungs of diabetic rats - Kurtz, Melisa Lidia Amelia (2014)
Maternal diabetes impairs fetal lung development. Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors relevant in lipid homeostasis and lung development. This study aims to evaluate the effect of in vivo activation of PPARs on lipid homeostasis in fetal lungs of diabetic rats. To this end, we studied lipid concentrations, expression of lipid metabolizing enzymes and fatty acid composition in fetal lungs of control and diabetic rats i) after injections of the fetuses with Leukotriene B4 (LTB4, PPARα ligand) or 15deoxyΔ12,14prostaglandin J2 (15dPGJ2, PPARγ ligand) and ii) fed during pregnancy with 6% olive oil- or 6% safflower oil-supplemented diets, enriched with PPAR ligands were studied. Maternal diabetes increased triglyceride concentrations and decreased expression of lipid-oxidizing enzymes in fetal lungs of diabetic rats, an expression further decreased by LTB4 and partially restored by 15dPGJ2 in lungs of male fetuses in the diabetic group. In lungs of female fetuses in the diabetic group, maternal diets enriched with olive oil increased triglyceride concentrations and fatty acid synthase expression, while those enriched with safflower oil increased triglyceride concentrations and fatty acid transporter expression. Both olive oil- and safflower oil-supplemented diets decreased cholesterol and cholesteryl ester concentrations and increased the expression of the reverse cholesterol transporter ATP-binding cassette A1 in fetal lungs of female fetuses of diabetic rats. In fetal lungs of control and diabetic rats, the proportion of polyunsaturated fatty acids increased with the maternal diets enriched with olive and safflower oils. Our results revealed important changes in lipid metabolism in fetal lungs of diabetic rats, and in the ability of PPAR ligands to modulate the composition of lipid species relevant in the lung during the perinatal period.